Risk factors for intestinal obstruction after Ladd procedure - Tetsuya Mitsunaga; Takeshi Saito; Keita Terui; Mitsuyuki Nakata; Sachie Ohno; Naoko Mise; Satoru Oita; Hideo Yoshida (MDPI AG, 2015)
Intestinal obstruction is a common complication after Ladd procedure. Ninety-three cases who had undergone the Ladd procedure between 1977 and 2013 treated at our own institution were retrospectively reviewed to identify the causes and risk factors for intestinal obstruction. The Ladd procedure has been performed without any intestinal fixing. Of the 87 cases who survived to discharge, intestinal obstruction was observed in 22 (25.3%). Among the cases with intestinal obstruction, 13 (59.1%) showed intestinal ischemia at the initial operation; this incidence was notably high, although it is low when only those cases with another concurrent surgical digestive disease are considered. All cases of intestinal obstruction were caused not by recurrent volvulus, but by adhesion between the intestine and the mesentery. Intestinal fixing is not required to prevent recurrent volvulus, but it is important to achieve adequate widening of the mesenteric base. The risk of intestinal obstruction after the Ladd procedure, on the other hand, is high. Moreover, patients with intestinal ischemia have an increased risk of intestinal obstruction.